The Effect and Dose-Response of Functional Electrical Stimulation Cycling Training on Spasticity in Individuals With Spinal Cord Injury: A Systematic Review With Meta-Analysis - Fang, Chia-Ying; Lien, Angela Shin-Yu; Tsai, Jia-Ling; Yang, Hsiao-Chu; Chan, Hsiao-Lung; Chen, Rou-Shayn; Chang, Ya-Ju (Frontiers in Physiology, 2021)
Background: To investigate the effect and dose-response of functional electrical stimulation cycling (FES-cycling) training on spasticity in individuals with spinal cord injury (SCI). Method: Five electronic databases (PubMed, Scopus, Medline (Proquest), Embase and Cochrane Central Register of Controlled Trials [CENTRAL]) were searched before September 2021. Only human trials and studies of English language were included. Two authors independently reviewed and extracted the searched studies. The primary outcome measure was spasticity assessed by Modified Ashworth Scale or Ashworth Scale for lower limbs. Secondary outcome measures were walking abilities including 6 Minute Walk Test, Timed Up and Go, and lower limbs muscle strength (LEMS). Subgroup analysis was performed to investigate the efficacious threshold number of training sessions. Meta-regression analysis was used to examine the linear relationship between the training sessions and the effect on spasticity. Results: A total of 764 studies were identified. After screening, twelve selected studies were used for qualitative synthesis, in which eight of them were quantitatively analyzed. The 8 studies included totally ninety-nine subjects with SCI (male: female= 83:16). The time since injury was from less than 4 weeks to 17 years. The age ranged from 20 to 67 years. The number of participants’ ASIA level was 59 for ASIA A, 11 for ASIA B, 18 for ASIA C, 11 for ASIA D. There were 43 subjects with tetraplegia and 56 subjects with paraplegia. Spasticity decreased significantly (95% CI= -1.538 to -0.182, p=0.013) in favor of FES-cycling training. The walking ability and LEMS also improved significantly in favor of FES-cycling training. The subgroup analysis showed that spasticity decreased significantly only in more than twenty training sessions (95% CI= -1.749 to -0.149, p=0.020). The meta-regression analysis showed training sessions and spasticity were not significantly associated (coefficient= -0.0025, SE= 0.0129, p=0.849, R2 analog= 0.37). Conclusion: FES-cycling training can improve spasticity, walking ability and the strength of the lower limbs in individuals with SCI. The number of training sessions is not linearly related to the decrease of spasticity. Twenty sessions of FES-cycling training are required to obtain the efficacy to decrease spasticity.